2000
DOI: 10.1193/1.1586082
|View full text |Cite
|
Sign up to set email alerts
|

New Site Coefficients and Site Classification System Used in Recent Building Seismic Code Provisions

Abstract: Recent code provisions for buildings and other structures (1994 and 1997 NEHRP Provisions, 1997 UBC) have adopted new site amplification factors and a new procedure for site classification. Two amplitude-dependent site amplification factors are specified: Fa for short periods and Fv for longer periods. Previous codes included only a long period factor S and did not provide for a short period amplification factor. The new site classification system is based on definitions of five site classes in terms of a repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
193
0
7

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 383 publications
(202 citation statements)
references
References 0 publications
2
193
0
7
Order By: Relevance
“…The 2003-NEHRP Provisions use a spectral shape anchored at two spectral accelerations (for short and long-periods that are extracted from hazard maps) and include building importance coefficients and non-linear, period-dependent soil amplification factors (Borcherdt 1994;Dobry et al 2000). Specifically, the 2003-NEHRP Provisions consider SA 247 5(0.2s) and SA2475(1.0s), the expected spectral accelerations of 0.2 and 1.0 with a 2% probability of exceedance in 50 years, equivalent to a return period of 2475 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2003-NEHRP Provisions use a spectral shape anchored at two spectral accelerations (for short and long-periods that are extracted from hazard maps) and include building importance coefficients and non-linear, period-dependent soil amplification factors (Borcherdt 1994;Dobry et al 2000). Specifically, the 2003-NEHRP Provisions consider SA 247 5(0.2s) and SA2475(1.0s), the expected spectral accelerations of 0.2 and 1.0 with a 2% probability of exceedance in 50 years, equivalent to a return period of 2475 years.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the large-scale approach used, it was unviable to perform site-specific analyses for assessing ground amplification factors, and these were obtained by averaging amplification factors proposed in the literature. Specifically, amplification factors for PGA (Table 3) account the non-linearity and period-dependency of soil response, amplification factors for spectral accelerations (Table 3) were adapted from the 2003 NEHRP Provisions (Dobry et al 2000). As the averaged PGA amplification factor calculated above does not correspond to the PGA amplification factor contained in the 2003 NEHRP Provisions, it was necessary to recalculate amplification factors for the short-period range (from 0.0 through 0.1 s).…”
Section: Seismic Hazard At Selected Sites Of the Region Of Murciamentioning
confidence: 99%
“…where superscript 'N' indicates re-normalization, F a and F v are the original, published NEHRP factors, V ref = 1050 m/s per Borcherdt (1994b) and Dobry et al (2000), and m a and m v are taken from Borcherdt (1994b) and Dobry et al (2000) (shown in Figure 4). No adjustments are made at PGA r = 0.5g due to a lack of published m a and m v values in Figure 4.…”
Section: Differences Between Nehrp and Nga Site Factors Site Factors mentioning
confidence: 99%
“…Similar considerations apply for nonlinear ground response analysis. Borcherdt (1994b) and Dobry et al (2000) describe the process by which equivalent linear and nonlinear ground response simulations were used to supplement the linear site factors in Figure 3. Suites of profiles were analyzed by Seed et al (1994) and for categories C-E using velocity profiles from sites in California and Mexico City.…”
Section: Simulation-based Nonlinearity In Nehrp Site Factorsmentioning
confidence: 99%
See 1 more Smart Citation